Antonio Conselheiro: a voz de Canudos. - Silva, Antonio José Villarim Alves da (2024)
The general objective of this Technical Report is to present a study on Belo Monte (Canudos) based on the book “Antônio Conselheiro por ele vida”, authored by Pedro Lima Vasconcellos, historian of religions and researcher of Belo Monte. Vasconcellos’ work is characterized by the transcription and analysis of the sermons given by Conselheiro, entitled “Notes on the precepts of the Divine Law of Our Lord Jesus Christ, for the Salvation of Men”. The notes bring meditations, specific and practical teachings on how to live in an environment that respects human dignity. Counselor became a socio-religious leader of Canudos, a kind of quilombo, located in the middle of the Bahian hinterland. He was someone who had the authority of the word, who had great knowledge about the Bible and the history of the medieval church His sermons and preaches dealt with important theological themes based on ethics and Christian values and attracted to Belo Monte black people, Indians, mulattoes, the underserved and the unfortunate who were problems for the republican government. As for the presentation of the product, it was prepared in a comic book format and didactic language, with the target audience being students in Elementary School and Final Years in public schools. The text is an adaptation of the transcription of the Counselor's Notes made by Pedro Vasconcellos and narrates the arrival of Antônio Conselheiro in Belo Monte and his career teaching and preaching to the unfortunate Belomontenses. The consultations carried out in different works contributed not only to the formation of the product, but also showed that the acts that occurred in Belo Monte have great historical, political, social and religious relevance for understanding the context experienced by Brazilians at the end of the 19th century.